The second son - Rabb, Jonathan (Sarah Crichton Books/Farrar, Straus and Giroux, 2011)
On the Eve of Hitler's Olympics, Chief Inspector Nikolai Hoffner is forced out of the Kriminalpolizei because he is a half Jew. Hoffner is not surprised given the rise of Nazism, and anyway his focus is elsewhere. His son Georg is missing in Spain, swept up in the sudden outbreak of the civil war. He has already lost Sascha, his elder son, to the Nazi regime. But Georg is not what he appears to be, and when Hoffner discovers this, he is determined to save the one son he can.